PENGARUH PEMAHAMAN PERPAJAKAN TENTANG TARIF PAJAK, SANKSI PAJAK, DAN KEADILAN PAJAK TERHADAP PERSEPSI MAHASISWA MENGENAI PENGGELAPAN PAJAK - Fitria, Kartika Indra; Wahyudi, Djoko (KRISNA: Kumpulan Riset Akuntansi, 2022)
The purpose of this study was to determine the effect of understanding tax rates, tax sanctions and tax justice partially on student perceptions of tax evasion. This study uses the slovin formula as many as 100 respondents. The research analysis method used is multiple linear regression analysis. The results of this study are the understanding of tax rates partially has a positive and significant effect on students' perceptions of tax evasion, partial tax sanctions have a positive and significant effect on students' perceptions of tax evasion, and tax justice partially has a positive and significant effect on students' perceptions of tax evasion. , and understanding of tax rates, tax sanctions, and tax justice simultaneously have a positive and significant effect on studts' perceptions of tax evasion.